Effect of Combined Warm Salt Water Foot Soak and Murottal Qur’an Therapy on Pain Levels in Gouty Arthritis: A Pre-Experimental Study - Isnaini Fidyatus Sa’adah; Virgianti Nur Faridah; Rizky Asta Pramestirini (Universitas Airlangga, 2026)
Introduction: Joint pain is a common complaint among adults and the older adults. Pain caused by gouty arthritis can be managed through both pharmacological and non-pharmacological approaches, including warm saltwater foot soak therapy and listening to Murottal Qur’an. This study aimed to investigate the effect of warm saltwater foot soak therapy combined with murottal Qur’an on pain levels in patients with gouty arthritis. Method: This study employed a pre-experimental one-group pretest-posttest design. The population consisted of 40 older adults with gouty arthritis who participated in the Integrated Health Development Post for Non-Communicable Diseases (Posbindu PTM) in a village in Indonesia. Total sampling was applied, and all respondents received a combined intervention of warm saltwater foot soaks and murottal Qur’an theraphy. Pain data were collected using the Numeric Rating Scale (NRS), observation sheet, and standard operating procedures (SOPs). Data were analyzed descriptively using minimum-maximum values, means, and percentages, followed by Wilcoxon signed-rank test with a significance level of 0.05. Results: Befor the intervention, most respondents (67.5%) experienced moderate pain (pain scale 4–6), with an mean pain score of 4.58 and a pain scale range of 2-8. After the intervention, the majority of respondents (90%) showed improvement, with pain levels decreasing to mild pain (pain scale 1–3), a mean pain score of 2.05, and a pain scale range of 1–4. The mean difference between pre- and post-intervention pain scores was 2.53. Furthermore, statistical analysis showed a significant difference in pain scores before and after the intervention (p < 0.05). Conclusions: Despite the limitations of the pre-experimental design, the findings suggest that the combination of warm saltwater foot soak and murottal Qur’an therapy may help reduce pain levels in patients with gouty arthritis. Further studies using randomized experimental designs are recommended to confirm the effectiveness of this combined theraphy.